A Thickened Coracohumeral Ligament and Superomedial Capsule Limit Internal Rotation of the Shoulder Joint: Report of Three Cases - Masashi Koide; Junichiro Hamada; Yoshihiro Hagiwara; Kenji Kanazawa; Kazuaki Suzuki (Case Reports in Orthopedics)
Adhesive capsulitis of the shoulder (also known as frozen shoulder) is a painful and disabling disorder with an estimated prevalence ranging from 2% to 5% in the general population. Although the precise pathogenesis of frozen shoulder is unclear, thickened capsule and coracohumeral ligament (CHL) have been documented to be one of the most specific manifestations. The thickened CHL has been understood to limit external rotation of the shoulder, and restriction of internal rotation of the shoulder has been believed to be related to posterior capsular tightness. In this paper, three cases of refractory frozen shoulder treated through arthroscopic release of a contracted capsule including CHL were reported. Two cases in which there is recalcitrant severe restriction of internal rotation after manipulation under anesthesia (MUA) were finally treated with arthroscopic surgery. Although MUA could release the posterior capsule, internal rotation did not improve in our cases. After release of the thickened CHL, range of motion of internal rotation was significantly improved. This report demonstrates the role of the thickened CHL in limiting the internal rotation of the shoulder. We highlight the importance of release of thickened CHL in addition to the pancapsular release, in case of severe limitation of internal rotation of shoulder.